2020
DOI: 10.1111/ans.16336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 national lockdown on emergency general surgery: Auckland City Hospital's experience

Abstract: Background: The New Zealand Government announced a four-level COVID-19 alert system soon after the first confirmed case in the country. New Zealand moved swiftly to the highest alert level 4, described as lockdown, as the epidemic curve quickly accelerated. Auckland City Hospital saw a temporary change in acute surgical admissions. The aim of this study is to evaluate the impact of the national lockdown on emergency general surgery. Methods: A retrospective analysis was performed of all patients admitted to Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 4 publications
5
37
0
7
Order By: Relevance
“…This study was confined to Northland which had low levels of COVID‐19 throughout the studied period, limiting the wider applicability. Contrary to many hospitals, no change to surgical management of acute general surgical patients was implemented in Northland in response to the possible increased risk of exposure to COVID‐19 from laparoscopic surgery 23 . This study's findings should also be interpreted through the lens of NZ's unique global situation with a comparatively rapid reversal of the epidemic curve following intense public health restrictions.…”
Section: Discussionmentioning
confidence: 87%
“…This study was confined to Northland which had low levels of COVID‐19 throughout the studied period, limiting the wider applicability. Contrary to many hospitals, no change to surgical management of acute general surgical patients was implemented in Northland in response to the possible increased risk of exposure to COVID‐19 from laparoscopic surgery 23 . This study's findings should also be interpreted through the lens of NZ's unique global situation with a comparatively rapid reversal of the epidemic curve following intense public health restrictions.…”
Section: Discussionmentioning
confidence: 87%
“…The data sheds light on the effect varying levels of public health intervention has on major trauma admissions with the largest decrease in the early intervention period. This was likely the time of greatest uncertainty and fear with limited information on NZ pandemic trajectory 6 . The largest differences in secondary outcomes were seen in the period of greatest public health restriction with the lowest number of RTCs and highest number of injuries at home across the study period in level 4 lockdown.…”
Section: Discussionmentioning
confidence: 98%
“…Since the onset of public health interventions to control the COVID‐19 pandemic there have been many reports outlining the effect of these interventions on general surgical trauma admissions from around the world 1,6–21 . Various methodologies have been employed with commonly short periods of time used and a time period before the interventions used as a comparator.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that due to the impact of the epidemic, patients have reduced their visits to hospitals for fear of increased risks of COVID-19 infection. [ 7 ] The number of visits to the department of emergencysurgery decreased, [ 16 ] as well as the number of patients in other disciplines, including the postponing of urinary surgical procedures, [ 17 ] decreased outpatient hemodialysis, [ 18 ] interruption of organ transplantation, [ 19 ] and so on. The incidence of acute appendicitis has also decreased, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%